2023
DOI: 10.15581/003.36.1.151-166
|View full text |Cite
|
Sign up to set email alerts
|

Online prosumer convergence: Listening, creating and sharing music on YouTube and TikTok

Abstract: Social media and prosumers have encouraged participatory creativity in the era of platformization. In this context, successful platforms such as YouTube and TikTok have facilitated users interact with music content in a wide variety of meaningful and evocative videos. In the light of research on the cultural prosumption of Internet content, as well as the global exchange of musical data, which is leading an emerging and innovative digital convergence, this study analyses the intersection between digital music … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…It has also been found that the integration of music into storytelling on social media platforms, such as YouTube and TikTok, has evolved beyond technological advances, in line with the relationship between users and social media (Vizcaíno-Verdú et al, 2023). This finding emphasizes the adaptable and dynamic nature of music in social media, which may evolve in response to shifting user preferences and platform characteristics.…”
Section: The Potential Of Music To Be Effective In "Story" and "Short...mentioning
confidence: 94%
See 1 more Smart Citation
“…It has also been found that the integration of music into storytelling on social media platforms, such as YouTube and TikTok, has evolved beyond technological advances, in line with the relationship between users and social media (Vizcaíno-Verdú et al, 2023). This finding emphasizes the adaptable and dynamic nature of music in social media, which may evolve in response to shifting user preferences and platform characteristics.…”
Section: The Potential Of Music To Be Effective In "Story" and "Short...mentioning
confidence: 94%
“…The convergence of social media and music has given rise to a new phenomenon known as prosumer convergence. Vizcaíno-Verdú et al (2023) discuss the concept of prosumer convergence in the context of music consumption on platforms like YouTube and TikTok. These platforms have enabled users to interact with music content in various ways, including listening, creating and sharing.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, it was evidenced that there are 3 types of fan theories (followers of a theme) that support and prioritize argumentative and creative mechanisms (Amo and García, 2022) and that the audiovisual displayed in the media can be considered texts of powerful and complex cultures (Goyez, 2021). Through a collaboration between Spanish and Italian authors, it was identified that the digital denotes importance in the life of users as a means to express themselves and relate to other people (Vizcaíno et al, 2022) and that the most active members are the administrators, content moderators and generators of conversations, which shows that they are those who have advanced digital skills and can perform tasks within the virtual community.…”
Section: Contents In Virtual Communitiesmentioning
confidence: 99%
“…For example, in Peru and Spain, through a collaboration, the content generated by prosumer users of mobile games, who disseminate content through social media storytelling on digital platforms, was investigated and analyzed (Yucra et al, 2022). In Spain and Italy, an analysis of the interrelationship of a digital music platform with consumer and prosumer users was sought (Vizcaíno et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of music, its popularity has not been exclusively dependent on the creativity or extensiveness its features. On TikTok, music engages followers and encourages trends by fostering a form of "music curation" through its audio element (Vizcaíno-Verdú, de-Casas-Moreno and Tirocchi, 2023), which has the potential to spread group storytelling dynamics (Vizcaíno-Verdú and Abidin, 2022).…”
Section: Introductionmentioning
confidence: 99%